Philippines : Recent Economic Developments. (IMF Staff Country Reports; Country Report, 1995)
This paper reviews economic developments in the Philippines during 1990-95. By 1994, all the elements for a strong recovery had finally fallen into place. Gross National Product (GNP) growth accelerated to 5 percent, fueled by a strong performance of investment and export-oriented manufacturing. Based on this favorable composition of growth, and a near 50 percent increase in remittances, the balance of payments improved. In stark contrast to the earlier recovery, the current account deficit narrowed by 1 percentage point to 4 1\2 percent of GNP.